Discrete-time internal model control with disturbance and vibration rejection. (January 2017) - De Keyser, Robin; Copot, Cosmin; Hernandez, Andres; Ionescu, Clara
This paper presents a novel design methodology for discrete-time internal model control (IMC) used to compute a disturbance filter. The proposed method employs a generalized algorithm for disturbance rejection and for process dynamics compensation. In IMC, the controller is designed based on a model of the process, while ensuring a desired closed loop performance trajectory (for setpoint tracking). However, in some situations, for example poorly damped systems, the open loop poles of the process affect the closed loop disturbance rejection dynamics. The novel design methodology presented is able to compensate both process dynamics and input disturbances. The method is validated both in simulations and in experimental tests on a poorly damped mass–spring–damper testbench.